2019
DOI: 10.1083/jcb.201902063
|View full text |Cite
|
Sign up to set email alerts
|

Loss of myosin Vb promotes apical bulk endocytosis in neonatal enterocytes

Abstract: In patients with inactivating mutations in myosin Vb (Myo5B), enterocytes show large inclusions lined by microvilli. The origin of inclusions in small-intestinal enterocytes in microvillus inclusion disease is currently unclear. We postulated that inclusions in Myo5b KO mouse enterocytes form through invagination of the apical brush border membrane. 70-kD FITC-dextran added apically to Myo5b KO intestinal explants accumulated in intracellular inclusions. Live imaging of Myo5b KO–derived enteroids confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 78 publications
(121 reference statements)
1
16
0
Order By: Relevance
“…We previously showed that apical bulk endocytosis mirrors neuronal activity–dependent bulk endocytosis requiring Pacsin2 and dynamin2 for inclusion formation. 16 The work presented here indicates that endocytic trafficking and polarity complexes are closely associated with the formation of inclusions via bulk endocytosis. Based on our findings, we postulate that MYO5B regulates multiple aspects of epithelial homeostasis, including cell polarity, tight junction protein distribution, and localization of ion transporters.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…We previously showed that apical bulk endocytosis mirrors neuronal activity–dependent bulk endocytosis requiring Pacsin2 and dynamin2 for inclusion formation. 16 The work presented here indicates that endocytic trafficking and polarity complexes are closely associated with the formation of inclusions via bulk endocytosis. Based on our findings, we postulate that MYO5B regulates multiple aspects of epithelial homeostasis, including cell polarity, tight junction protein distribution, and localization of ion transporters.…”
Section: Discussionmentioning
confidence: 66%
“…Intestinal organoids require differentiation to develop robust inclusion formation. 16 , 65 Inclusion formation in DMSO and ζ-Stat treatment resulted in a similar number of inclusions identified by F-actin staining ( Figure 9 A ). Therefore, treatment of Myo5b KO intestinal organoids with ζ-Stat did not prevent inclusion formation, suggesting that inclusion formation is not entirely dependent on aPKC or that there are redundancies in the functions of polarity proteins.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations